Water and Development : World Bank Support, 1997-2007 - World Bank (Washington, DC, 2012)
Almost a third of all Bank projects approved since 1997 have been water related. Water lending grew 55 percent in commitment terms during the period evaluated, and project performance has improved steadily, led by a significant performance improvement in the Africa region. Water has been integrated into many other sectors. The Bank has contributed to improving access to clean water, especially in urban areas, and has developed a business plan for investments in hydropower and dams, especially for Africa. The Bank is also starting to take the aquatic environment more into account during project design, and it has balanced investments in infrastructure with investments in improving the institutions that manage and allocate water. The Bank's strategy for the water sector has been broadly appropriate, but its application has underemphasized some of the most difficult challenges-such as ground water conservation, environmental restoration, and coastal zone management-in favor of less challenging activities like infrastructure development and equipment purchase. The Bank's approach to water will face heightened challenges in the coming decades due to climate change, the migration to coastal zones, and the declining quality of the water resources available to most major cities and industry. This will require some shifts in emphasis. The Bank and its partners need to put more emphasis on vital and challenging areas such as groundwater conservation, pollution reduction, and effective demand management. New ways need to be found to help the most water-stressed countries make water sustainability a corner-stone of their development. The development community needs to help countries shift more attention to sanitation. More strategic development planning and more effective disaster risk reduction is needed for low-lying coastal areas. Approaches to financing and cost recovery need to be strengthened. Finally, data collection and use need to be enhanced in a number of areas.